Immature stages of Heraclides thoas thoas (Linnaeus, 1771) (Lepidoptera: Papilionidae): biology and morphology - Graça, Márlon Breno Costa Santos da; Nunes-Gutjahr, Ana Lúcia (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
The morphology and biological aspects of the immature stages of Heraclides thoas thoas (Linnaeus, 1771) (Lepidoptera: Papilionidae) are described. Eggs of H. thoas thoas were collected in Belém, Pará, Brazil, and larvae were reared on Piper aduncum L. (Piperales: Piperaceae). Parasitism by Sarcodexia lambens (Wiedemann, 1830) (Diptera: Sarcophagidae) in the pupal stage was observed.